ACADEMIC SUPERVISION STRATEGIES BY SCHOOL PRINCIPALS BASED ON AUTHENTIC OBSERVATION: EFFORTS TO DEVELOP TEACHER PROFESSIONALISM AT MADRASAH MASANEMA - Khoirul Roziqin; Ali Imron; Sunarni Sunarni (LP2M IAI Al-Khairat Pamekasan, 2026)
This study was motivated by the importance of academic supervision as one of the strategies employed by school principals to enhance teachers’ professional competencies, given that supervision practices still tend to be administrative in nature and are not yet fully oriented toward continuous professional development. This study aims to describe and analyze the stages of implementation of school principals’ academic supervision in enhancing teachers’ professional competencies through the aspects of planning, implementation, evaluation, and follow-up of supervision at Madrasah Masanema. The study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation with informants comprising the madrasah principal, the curriculum vice principal, senior teachers, and junior teachers. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, while data validity was tested through triangulation of sources and techniques. The results of the study indicate that academic supervision is implemented through systematic planning, implementation based on authentic observation—including the review of teaching materials and direct classroom observation—team-based evaluation, and follow-up tailored to teachers’ needs through training, mentoring, and reflective discussions. This study concludes that academic supervision based on authentic observation is capable of continuously improving teachers’ professional competencies and has the potential to become an effective professional development model for improving the quality of learning in Madrasah.